KESESUAIAN SARANA DAN PRASARANA PADA SEKOLAH DASAR LUAR BIASA C DI KOTA MALANG - Defribian, Stephanie; Handajani, Rinawati P. (Jurnal Mahasiswa Jurusan Arsitektur, 2020)
As the second biggest city in East Java, Malang City has a concern where the social welfare adds up 544 are children (Social Service Secretariat, 2019), because of that conformity facilities and equipment became urgency because too many children with mental retardation in Malang. This study uses The 2008 Minister of Education Regulation Number 33 about standard facilities and equipment for Elementary School Special Education, Middle High School Special Education, and Senior High School. This study research facilities and equipment inside the main room, special room, and some other room that often being used by the children. These sample being chosen from 8 elementary school special education in Malang City by non-probability sampling with purposive sampling with the criteria are elementary school for mental retardation. This research is quantitative research. Later on, the results being served in a percentage number and being explained with descriptive. The result of conformity facilities and equipment are  36% for SDLB Sumber Dharma, 46% for SDLB C Kedungkandang, and 57% for SDLB Bhakti Luhur. This means, there is still a lot of discrepancy with the standard, that should have been fulfilled perfectly to support the learning activity especially for students with mental retardation.